Respuesta :
1.) Given the equation of a parabola
[tex]y = 12x^2+6x+24[/tex]
The vertex form of a parabola is given by
[tex]y-k=a(x-h)^2=4p(x-h)^2[/tex]
where: (h, k) is the vertex and p is the distance between the vertex and the directrix.
[tex]y = 12x^2+6x+24 \\ = 12(x^{2} + \frac{1}{2} x)+24 \\ = 12(x^{2} + \frac{1}{2} x+ \frac{1}{16}) +24- \frac{3}{4} \\ =12(x+ \frac{1}{4} )^2+ \frac{93}{4} \\ y-\frac{93}{4}=4(3)(x+ \frac{1}{4} )^2[/tex]
From the equation, the vertex is [tex](- \frac{1}{4} , \, \frac{93}{4} )[/tex] and the distance between the vertex and the directrix is 3.
Because, the x-part of the equation is squared and the value of p is positive, this means that the parabola opens up and the directrix is a horizontal line having the value y = c, where c is the y-value of the vertex - 3
Equation of the directrix is [tex]y= \frac{93}{4}-3= \frac{81}{4} [/tex]
Therefore, the equation of the directrix is [tex]y=\frac{81}{4} [/tex]
2.) Given the equation of a parabola written in vertex form
[tex](y-1)^2 = 16(x+3)[/tex]
The vertex form of a parabola is given by
[tex](y-k)^2=a(x-h)=4p(x-h)[/tex]
where: (h, k) is the vertex and p is the distance between the vertex and the directrix.
[tex](y-1)^2 = 16(x+3)=4(4)(x+3)[/tex]
From the equation, the vertex is [tex](-3 , \, 1)[/tex] and the distance between the vertex and the directrix is 4.
Because, the y-part of the equation is squared and the value of p is positive, this means that the parabola opens to the right and the directrix is a vertical line having the value x = c, where c is the x-value of the vertex - 4
Equation of the directrix is [tex]x= -3-4= -7 [/tex]
Therefore, the equation of the directrix is [tex]x= -7[/tex]
[tex]y = 12x^2+6x+24[/tex]
The vertex form of a parabola is given by
[tex]y-k=a(x-h)^2=4p(x-h)^2[/tex]
where: (h, k) is the vertex and p is the distance between the vertex and the directrix.
[tex]y = 12x^2+6x+24 \\ = 12(x^{2} + \frac{1}{2} x)+24 \\ = 12(x^{2} + \frac{1}{2} x+ \frac{1}{16}) +24- \frac{3}{4} \\ =12(x+ \frac{1}{4} )^2+ \frac{93}{4} \\ y-\frac{93}{4}=4(3)(x+ \frac{1}{4} )^2[/tex]
From the equation, the vertex is [tex](- \frac{1}{4} , \, \frac{93}{4} )[/tex] and the distance between the vertex and the directrix is 3.
Because, the x-part of the equation is squared and the value of p is positive, this means that the parabola opens up and the directrix is a horizontal line having the value y = c, where c is the y-value of the vertex - 3
Equation of the directrix is [tex]y= \frac{93}{4}-3= \frac{81}{4} [/tex]
Therefore, the equation of the directrix is [tex]y=\frac{81}{4} [/tex]
2.) Given the equation of a parabola written in vertex form
[tex](y-1)^2 = 16(x+3)[/tex]
The vertex form of a parabola is given by
[tex](y-k)^2=a(x-h)=4p(x-h)[/tex]
where: (h, k) is the vertex and p is the distance between the vertex and the directrix.
[tex](y-1)^2 = 16(x+3)=4(4)(x+3)[/tex]
From the equation, the vertex is [tex](-3 , \, 1)[/tex] and the distance between the vertex and the directrix is 4.
Because, the y-part of the equation is squared and the value of p is positive, this means that the parabola opens to the right and the directrix is a vertical line having the value x = c, where c is the x-value of the vertex - 4
Equation of the directrix is [tex]x= -3-4= -7 [/tex]
Therefore, the equation of the directrix is [tex]x= -7[/tex]
Answer: The equation of directrices are
(1) [tex]y=\dfrac{81}{4}[/tex]
(2) [tex]x=-7.[/tex]
Step-by-step explanation: We are given to find the equation of the directrices of the following parabolas:
[tex]y=12x^2+6x+24~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\(y-1)^2=16(x+3)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]
(1) The equation of the directrix for the parabola [tex](y-k)=4p(x-h)^2,[/tex] is given by
[tex]y=k-p.[/tex]
From equation (i), we have
[tex]y=12x^2+6x+24\\\\\Rightarrow y=12\left(x^2+\dfrac{1}{2}x\right)+24\\\\\\\Rightarrow y=12\left(x^2+2\times x\times \dfrac{1}{4}+\dfrac{1}{16}\right)-\dfrac{12}{16}+24\\\\\\\Rightarrow y=12\left(x+\dfrac{1}{4}\right)^2-\dfrac{3}{4}+24\\\\\\\Rightarrow y=4\times 3\left(x+\dfrac{1}{4}\right)^2+\dfrac{93}{4}\\\\\\\Rightarrow y-\dfrac{93}{4}=4\times 3\left(x+\dfrac{1}{4}\right)^2.[/tex]
Comparing with the standard equation, we get
[tex]k=\dfrac{93}{4},~~p=3.[/tex]
So, the equation of the directrix is
[tex]y=k-p\\\\\Rightarrow y=\dfrac{93}{4}-3\\\\\\\Rightarrow y=\dfrac{81}{4}.[/tex]
(2) The equation of the directrix for the parabola [tex](y-k)^2=4p(x-h),[/tex] is given by
[tex]x=h-p.[/tex]
From equation (i), we have
[tex](y-1)^2=16(x+3)\\\\\Rightarrow (y-1)^2=4\times4(x+3).[/tex]
Comparing with the standard equation, we get
[tex]h=-3,~~p=4.[/tex]
So, the equation of the directrix is
[tex]x=h-p\\\\\Rightarrow x=-3-4\\\\\Rightarrow x=-7.[/tex]
Thus, the equation of directrices are
(1) [tex]y=\dfrac{81}{4}[/tex]
(2) [tex]x=-7.[/tex]